How nanoparticles can induce dimerization and aggregation of cells in blood or lymph. (December 2021) - Zhdanov, Vladimir P.
Abstract: By analogy with virions, the binding of biologically-inspired nanoparticles (NPs) with ligands to the cellular membrane containing receptors depends on the multivalent ligand–receptor interaction, membrane bending, and cytoskeleton deformation. The interplay of these factors results in the existence of the potential minimum and activation barrier on the pathway towards full absorption of a NP. Herein, I hypothesize and show theoretically that the interaction of a NP, bound to one cell, with another cell can stabilize the potential minimum and increase the corresponding activation barrier, i.e., NPs can mediate the formation of long-living pairs of cells and aggregates containing a few cells inside blood and lymphatic vessels.